Examining the Influence of Ownership Structures on Firm Value Through Shariah-Compliant Profitability: An Empirical Study on Islamic Firms - Indah Wahyuni Sitohang (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This study investigates the impact of various ownership structures—managerial, institutional, foreign, and domestic—on the value of Sharia-based companies, with profitability as a mediating variable. Employing a quantitative approach grounded in positivism, the research examines companies listed on the Sharia Stock Exchange from 2019 to 2022. A systematic methodology is used, involving variable identification, data collection, and statistical analysis using Econometric Views (Eviews) 9 through a multiple regression model. The sample comprises 30 companies from the JII index, selected via purposive sampling, and uses balanced panel data. The results indicate that managerial (p = 0.5551), institutional (p = 0.0922), foreign (p = 0.8073), and domestic ownership (p = 0.0651) do not significantly influence firm value when mediated by profitability. Consequently, the hypotheses are rejected, demonstrating that ownership structures alone do not enhance firm value through profitability in Sharia-based companies. These findings contribute to the understanding of ownership-performance dynamics and highlight the necessity to consider additional factors affecting firm value